2001
DOI: 10.1128/jb.183.9.2918-2928.2001
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Stress-Induced Changes in Autoinducer AI-2 Production in Chemostat-Cultivated Escherichia coli K-12

Abstract: Numerous gram-negative bacteria employ a cell-to-cell signaling mechanism, termed quorum sensing, for controlling gene expression in response to population density. Recently, this phenomenon has been discovered in Escherichia coli, and while pathogenic E. coli utilize quorum sensing to regulate pathogenesis (i.e., expression of virulence genes), the role of quorum sensing in nonpathogenic E. coli is less clear, and in particular, there is no information regarding the role of quorum sensing during the overexpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
98
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 98 publications
(103 citation statements)
references
References 57 publications
5
98
0
Order By: Relevance
“…This suggests YncC functions at the late exponential stage and stationary stage, which are consistent with the finding that the homolog of E. coli yncC in the Gram-negative bacterium Salmonella enterica serovar typhimurium is under the regulation of the stationary-phase sigma factor s S (RpoS) (Ibanez-Ruiz et al, 2000). This mimics bacterial AI-2 internalization behavior (Xavier and Bassler, 2005) and also agrees with the concept that RpoS is intimately associated with E. coli quorum sensing (DeLisa et al, 2001a), which suggests that the quorum-sensing process, stress response process and biofilm development are tightly linked.…”
Section: Yncc Represses Ybimsupporting
confidence: 77%
“…This suggests YncC functions at the late exponential stage and stationary stage, which are consistent with the finding that the homolog of E. coli yncC in the Gram-negative bacterium Salmonella enterica serovar typhimurium is under the regulation of the stationary-phase sigma factor s S (RpoS) (Ibanez-Ruiz et al, 2000). This mimics bacterial AI-2 internalization behavior (Xavier and Bassler, 2005) and also agrees with the concept that RpoS is intimately associated with E. coli quorum sensing (DeLisa et al, 2001a), which suggests that the quorum-sensing process, stress response process and biofilm development are tightly linked.…”
Section: Yncc Represses Ybimsupporting
confidence: 77%
“…In chemostat experiments, pulses of glucose, iron or NaCl induced the up-regulation of AI-2 production by E. coli K-12, whereas others, e.g. heat shock, ethanol or H # O # , decreased AI-2 activity (DeLisa et al, 2001a). These data suggest that AI-2 production and degradation are tightly linked with the physiological and metabolic state of the cells.…”
Section: Introductionmentioning
confidence: 61%
“…Recently DeLisa et al (12) reported that transcriptional fusions containing only the promoter Q2p of ftsQ were upregulated threefold in response to quorum sensing through AI-2. Promoter Q2p is controlled by SdiA; these results would reflect an increase in SdiA production, which is consistent with our observation that there is a ca.…”
Section: Discussionmentioning
confidence: 99%